IN-VITRO CYTOTOXIC AND APOPTOSIS STUDY OF CHEMICAL CONSTITUENTS OF CLERODENDRUM PHLOMIDIS LEAF ON MCF-7 BREAST AND A-549 LUNG CANCER CELL LINES. - N, Habeela Jainab; Maruga Raja Mk, Mohan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Cancer is a molecularly heterogeneous diseaseand the leading cause of death worldwide. The methanol extract of Clerodendrum phlomidis leaf has been reported for cytotoxicity. Hence, the current investigation was planned to evaluate the cytotoxic activity of the chemical constituents isolated from the methanol extract of the C. phlomidis leaf against the Michigan cancer foundation-7 (MCF-7) breast cancer and adenocarcinomic human alveolar basal epithelial cells (A549) lung cancer cell lines by the apoptotic study. Methods: Cytotoxic activity of the chemical constituents of the methanol extract of the C. phlomidis leaf was evaluated by the 3-(4,5-dimethylthiazol- 2-yl)-5-diphenyltetrazolium bromide (MTT) assay against breast cancer (MCF-7) and lung cancer (A549) cell lines. The MCF-7 and A549 cell lines were tested at different concentrations to determine 50% of growth inhibition (inhibitory concentration [IC50]) by MTT assay. Apoptosis of nuclei was detected by 4',6-diamidino-2-phenylindole staining assay. Results: In MCF-7 breast cancer cell line study, Compounds 6 and 9 exhibited good cytotoxic activity with an IC50 value of 83.80 and 75.16 Î¼g/ml, respectively. In A549 lung cancer cell line, again Compounds 6 and 9 exhibited good cytotoxic activity with an IC50 value of 84.46 and 78.60 Î¼g/ml, respectively. Percentage of apoptosis induced by the Compounds 6 and 9 in the MCF-7 cancer cells was found to be 74.50 and 85.48, respectively. Conclusion: The results of the current study prove that the Compounds 6 and 9 are potential agents for breast and lung cancer. In future research, these potential agents can further be evaluated by animal studies and their mechanism of action apart from the induction of apoptosis of the cancer cells can be determined.